Pengembangan Life Skill Siswa Melalui Kreasi Mading di MA Bahrul Ulum Ngaglik Cerme Pace Nganjuk - Slamet Arofik; Ahmad Saifuddin (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The results of social analysis (Ansos) state that internally at MA Bahrul Ulum Ngaglik there are no vehicles or media that can be used as a means of developing Human Resources (HR) for their students. In these institutions intellectual and creative talents such as writing, composing poetry, composing, and even drawing are wasted without channeling because there is no available channel for distribution such as magazines, tabloids, scientific journals and even wall magazines (Mading). Even though it is common in an educational institution which in fact is an educational institution, teaches and equips students with various skills and skills that will be beneficial and useful, especially later when they take part in real life. There fore the STAI Darussalam service team will hold training in order to improve the Human Resources of their students through training on Wall Magazine creation (Mading). The method used uses the ABCD approach with the service learning model.